2020
DOI: 10.1088/2631-8695/aba1a1
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the effect of cutting parameters and tool nose radius on forces, machining power and tool life in face milling of ductile iron and validation using finite element analysis

Abstract: In the present study, the effect of cutting speed, feed rate, and tool nose radius on the forces, cutting power and tool life has been investigated in machining ductile iron. Face milling inserts with 0.8 mm and 2 mm corner radii were tested at three different cutting speeds and feed rates. The experiments were conducted using a full factorial design method and the Analysis of Variance (ANOVA) technique was used to determine the significance of each variable that is responsible for the variation in forces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Generally, the surface roughness of a machining operation can be controlled by optimizing the cutting parameters [23] or by changing the geometrical features of the tool like corner radius and wiper facet [24]. However, the work-material-dependent properties like composition, mechanical, and metallurgical properties also play a role in determining the surface roughness.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Generally, the surface roughness of a machining operation can be controlled by optimizing the cutting parameters [23] or by changing the geometrical features of the tool like corner radius and wiper facet [24]. However, the work-material-dependent properties like composition, mechanical, and metallurgical properties also play a role in determining the surface roughness.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…A similar trend was seen for the Fz forces as well. It can also be seen that increasing the cutting speed decreases all the three force components linearly, which is due to the thermal softening of work material at higher cutting speeds that make the tool easier to penetrate and shear [21]. Researchers have reported that cutting speed has the highest impact on the tool-chip interface temperature when compared to feed rate, which results in the softening of work material at the cutting zone.…”
Section: Forcesmentioning
confidence: 96%
“…The ANOVA table (Table 7) also confirms that the micro-geometry on the cutting and wiper edge has the highest significance of around 76% and 80.9% in determining the Ra and Rz values respectively followed by cutting speed with a significance of 6.65% and 5.95% respectively. Theoretically, the feed rate has a higher impact on the surface roughness rather than the cutting speed [21]. However, surprisingly, feed is seen as the third significant factor, which could be due to the presence of the wiper edge on all the four From the main effect and interaction plots (Figures 5 and 6), it can be interpreted that Insert B gives the superior surface finish values, whereas Insert A produces the least quality surface, which is in line with the trend seen in the Figures 3 and 4.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Abrasive wear, notching wear, and diffusion wear is predominantly found. Padmakumar et al [11] studied the effects of cutting on cutting forces, cutting power, and tool life while machining ductile iron. The tool nose radius is highly dominated for developing the cutting forces.…”
Section: Introductionmentioning
confidence: 99%